Clinical Outcomes of Patients with Methicillin-Resistant Staphylococcus aureus (MRSA) Bacteremia Treated with Vancomycin at an Institution with Suppressed Minimum Inhibitory Concentration (MIC) Reporting: Impact of Vancomycin MIC. (4th October 2017) - Adani, Shaili; Bhowmick, Tanaya; Weinstein, Melvin; Narayanan, Navaneeth
Abstract: Background: Recently, there have been several inconsistent analyses on the relationship between vancomycin MIC in MRSA bacteremia and clinical outcomes including mortality. The objective of this study was to determine whether treatment with vancomycin is associated with inferior clinical outcomes with a vancomycin MIC=2. Methods: This was a retrospective observational cohort study of patients with MRSA bacteremia treated with vancomycin for ≥72 hours from January 2013 to August 2016. The control arm consisted of MRSA isolates with a vancomycin MIC<2 and the active arm included isolates with a vancomycin MIC=2. Analysis of baseline characteristics included demographics, antimicrobial therapy, Charlson comorbidity index, Pitt bacteremia score, ID consultation, and other clinical characteristics. MICs were determined by broth microdilution via automated susceptibility testing (Microscan ® 01/2013–07/2015 and BD Phoenix™ 08/2015–08/2016). The primary outcome was 30-day in-hospital mortality. Secondary outcomes included duration of bacteremia, persistent bacteremia >7 days, recurrence within 30 days, change to alternative antibiotic therapy, and hospital length of stay. Multivariate analysis was conducted to control for potential confounding variables. Results: There were a total of 166 patients that met the inclusion criteria with 91 patients in the MIC<2 arm and 75 patients in the MIC=2 arm. The primary outcome, 30-day in-hospital mortality, was not significantly different in the MIC<2 arm as compared with the MIC=2 arm (13.2% vs. 24%, P = 0.072, respectively). Multivariate analysis showed no significant association of MIC=2 and 30-day in-hospital mortality (odds ratio, 1.57; 95% CI 0.60- 4.08), but demonstrated age and Pitt bacteremia score to be independent predictors. All secondary outcomes showed no statistically significant differences between study arms. Conclusion: Vancomycin therapy for MRSA bacteremia demonstrated no significant difference in clinical outcomes when assessing efficacy for isolates with a vancomycin MIC=2 compared with an MIC<2. Additional prospective studies with larger sample sizes are recommended to further validate these conclusions. Disclosures: All authors: No reported disclosures.